2017
DOI: 10.1371/journal.pone.0178247
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise does not modify brain activity and memory performance in APP/PS1 mice

Abstract: Age is the main risk factor for Alzheimer´s disease (AD). With an increasingly aging population, development of affordable screening techniques to determine cognitive status will help identify population-at-risk for further follow-up. Because physical exercise is known to modulate cognitive performance, we used it as a functional test of cognitive health. Mice were submitted to treadmill running at moderate speed for 30 min, and their brain activity was monitored before and after exercise using electrocorticog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Moreover, IGF-I administration can prevent loss of cognitive performance in humans [ 51 ]. According to these findings, our previous studies have also indicated that an IGF-I increase induced by exercise improves memory in young mice [ 52 ].…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, IGF-I administration can prevent loss of cognitive performance in humans [ 51 ]. According to these findings, our previous studies have also indicated that an IGF-I increase induced by exercise improves memory in young mice [ 52 ].…”
Section: Discussionsupporting
confidence: 56%
“…Whether the exercise intervention is applied chronically or acutely also seems to be an important factor determining whether a benefit is derived in mice with AD. This was shown recently by Stein et al who showed an acute bout of exercise was beneficial in littermate WT controls, improving spatial memory, but had no effect in AD transgenic mice [ 106 ]. These findings support the findings in human studies which suggest A pathology is not a reliable predictor of cognition in patients with AD, and that other factors such as neurogenesis may play larger roles in modulating cognitive decline.…”
Section: Exercise and Ad Protectionmentioning
confidence: 79%
“…It is known that exercise stimulates brain entrance of circulating IGF-I, which mediates many beneficial exercise actions in the brain (Carro et al, 2000 ; Trejo et al, 2001 ). Indeed, our previous findings indicated that physical exercise activates the EEG, increasing the hippocampal theta rhythm and improving memory in healthy mice, suggesting that the exercise-evoked increase of IGF-I may favor cortical activity and memory processes (Miki Stein et al, 2017 ). In addition, there are also pathological situations in which circulating IGF-signaling is decreased, such as diabetes and Alzheimer’s disease (Torres-Aleman, 2005 ; Fernandez et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%